What More Can We Learn from R&D Alliances? A Review and Research Agenda. Issue 3 (July 2018) - Martínez-Noya, Andrea; Narula, Rajneesh
R&D cooperation has become a core aspect of the innovation strategy of R&D-performing organisations over the last three decades. Globalization has increased the imperative to organise these cross-border, inter-firm agreements efficiently, and this has led to a cross-fertilisation of ideas from a variety of fields, including international business, management, geography and, more recently, psychology. The aim of this paper is to review and synthesise this literature to identify new directions for research. The breadth of the academic discussion has evolved towards a general consensus on governance choice decisions, motives for collaboration, partner selection decisions and performance implications. Despite having achieved some degree of clarity on these issues, the growing complexity and international nature of these alliances requires a multidisciplinary approach, both in relation to the theories to apply, as well as in the type of data needed.